2022
DOI: 10.3390/vaccines10122017
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Four COVID-19 Vaccines across Primary Doses 1, 2, 3 and Booster: A Prospective Cohort Study of Australian Community Pharmacy Vaccinations

Abstract: Four COVID-19 vaccines are approved for use in Australia: Pfizer-BioNTech BNT162b2 (Comirnaty), AstraZeneca ChAdOx1 (Vaxzevria), Moderna mRNA-1273 (Spikevax) and Novavax NVX-CoV2373 (Nuvaxovid). We sought to examine adverse events following immunisation (AEFI) at days 3 and 42 after primary doses 1, 2, 3 and booster. We conducted active vaccine safety surveillance from 130 community pharmacies in Australia integrated with AusVaxSafety, between August 2021–April 2022. Main outcomes: AEFI at 0–3 days post-vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Our findings on AE for which medical care was sought are consistent with previous findings by a prospective cohort study performed in Australia [23]. In our study, headache, fatigue and fever were the most commonly reported AE.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings on AE for which medical care was sought are consistent with previous findings by a prospective cohort study performed in Australia [23]. In our study, headache, fatigue and fever were the most commonly reported AE.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings on AE for which medical care was sought are in correspondence with previous findings by a prospective cohort study performed in Australia (17). In our study, headache, fatigue and fever were most commonly reported AE.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, some are calling for healthcare workers and certain other professionals to receive vaccines of lower reactogenicity [35]. Based on the findings of this and prior studies [37,[39][40][41][42][43][44], NVX-CoV2373 may provide a less reactogenic option for these individuals.…”
Section: Discussionmentioning
confidence: 86%
“…Notably, the referenced clinical studies were small and not designed to compare vaccine-associated side effects by vaccine type. Despite this, the consistency of reported reactogenicity event trends across various booster and primary series studies is clear [ 37 , 39 , 40 , 41 , 43 , 44 ]. Here, 2019nCoV-406 offers new real-world insights and an examination of human behavior associated with differences in reactogenicity.…”
Section: Discussionmentioning
confidence: 99%